A new parameter of statistic equality of sampling lengths in surface roughness measurement - Tomov, Mite (Strojniški vestnik, 2013)
This paper presents the procedure for obtaining the primary profile, the waviness profile, and the roughness profile when measuring surface roughness, based on a set of recommendations from several ISO standards. An analysis was conducted and key insights into the procedure are given. In addition, a proposal to introduce a new parameter of statistical equality of sampling lengths when measuring surface roughness is included and the possible benefits from introducing the new parameter are stated.
Keywords: mean value; parameter of statistical equality of sampling lengths; parameter statistične enakosti referenčnih dolžin; površinska hrapavost; primarni profil; primary profile; profil hrapavosti; profil valovitosti; roughness profile; srednja vrednost; standard deviation; standardna deviacija; surface roughness; waviness profile